The impact of the COVID-19 pandemic on academic performance among developmental age students: a systematic review with meta- analysis - Gianfredi, Vincenza; Scarioni, Simona; Marchesi, Luca; Ticozzi, Elena Maria; Addo, Martina Ohene; D'Errico, Valeriano; Frantantonio, Lorenzo; Liguori, Ludovica; Pellai, Alberto; Castaldi, Silvana (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Objective. The COVID-19 pandemic has disrupted educational systems worldwide, raising concerns about its impact on academic performance, particularly among developmental age students. Methods. A systematic review with meta-analysis aimed to evaluate the association between the COVID-19 pandemic and the academic performance in this population was performed according to PRISMA 2020 guidelines. PubMed/MEDLINE, Scopus and Embase were searched on December 2023 to identify relevant studies. Both fixed and random effect models were performed. The Effect size was reported as Cohen’s d with a 95% Confidence Interval. Studies’ quality was assessed using the Newcastle-Ottawa scale. The protocol was registered in PROSPERO. Results. A total of 30 studies met the inclusion criteria, but only 13 could be combined in the meta-analysis. Based on a sample size of 4,893,499 students, pooled Cohen’s d was -0.07 [(95% CI = -0.10; -0.03); p-value